Understanding and Analysing the Coordinates of Diversity of Wetland Birds of Asan Barrage near Paonta Sahib, Northern India (Our Nature, 2014)
The winter migratory wetland bird’s diversity of Asan barrage, Uttarakhand, India has been studied during 2005-2012. A total 60 species of wetland birds belonging to 6 orders and 13 families were observed. The findings also hints that Rudy Shelduck Tadorna ferruginea is the most dominant bird followed by Common Coot Fulica atra, Red-crested Pochard Rhodonessa rufina, Common Pochard Aythya ferina and Mallard Anas platyrhynchos. It was observed that Rudy Shelduck preferred Yamuna River waters rather than the traditional still pools, ponds, reservoirs etc. The same trend was displayed by Red-crested Pochard and Great-crested Grebe. On the contrary, winter migratory birds like Northern Shoveller Anas clypeata, Northern Pintail Anas acuta, Common Teal Anas crecca etc were found least in number at Asan Barrage but found in impressive numbers in Haryana traditional pools, ponds.DOI: http://dx.doi.org/10.3126/on.v11i2.9599 Our Nature 2013, 11(2): 192-200